THE INFLUENCE OF LEARNING MEDIA USABILITY AND LEARNING MOTIVATION ON STUDENT LEARNING OUTCOMES IN ECONOMICS SUBJECT IN THE 2022/2023 ACADEMIC YEAR: Study on Class XI Students of Private High Schools at Sanggar 016 DKI Jakarta - Heru Prasetio; Suparno Suparno; Sri Indah Nikensari (Yayasan Education and Social Center, 2023)
Conducted this research to analyze the effect of the usability of learning media on student learning outcomes in Economics subjects with learning motivation as an intervening variable. This research was conducted for 3 (three) months, from July to October 2022. The method used is a survey method using a quantitative approach. The study of the population was all Class XI IPS students in private high schools in the Sanggar 16 East Jakarta area, totaling 223 students. Determination of the number of samples using the Slovin formula and obtained a total sample of 143 students selected using the proportional random sampling technique. The collection technique uses the survey method with a closed questionnaire via Google Forms. The data used in this study are primary data for the independent variable (X) and secondary data for the dependent variable (Y). Data analysis used path analysis techniques with IBM SPSS Statistics 25. The results of this study indicate that: 1) the usability of learning media has a positive and significant effect on learning motivation, 2) the usability of learning media has a positive and significant effect on learning outcomes, 3) learning motivation has a positive and significant effect on learning outcomes, and 4) the usability of learning media has a positive and significant effect on student learning outcomes in class XI economics with learning motivation as an intervening variable